University proceedings. Volga region. Social sciences - A.A. Minin (Известия высших учебных заведений. Поволжский регион: Общественные науки)
Background. The relevance of the study is driven by the significant increase in the number of international students studying at universities in Saratov region and their important role in the educational and social life of the region. International students face various challenges during adaptation, including financial difficulties, language barriers, and cultural differences. The purpose of the study is to analyze the features of the socio-economic adaptation of international students and identify the key factors affecting their successful integration into the educational environment. Materials and methods. The study was conducted using in-depth interviews and surveys among international students at uni-versities in the Saratov region. The research included three main studies: identification of adaptation difficulties (n = 9), analysis of employment (n = 200), and financial strategies of students (n = 200). Results. The study revealed that 90 % of students experience financial difficulties, which prevent them from fully covering the costs of accommodation and tui-tion. The main areas of student employment include food services (40 %), delivery services (30 %), and taxi driving (16 %). While working, students aim to improve their financial situation, but balancing work and study leads to reduced academic performance. Average monthly expenses range from 19,500 rubles (minimum required) to 45,600 rubles (comfort-able level), and annual expenses range from 234,000 to 547,200 rubles. Conclusions. The main problem faced by international students is the lack of financial resources to cover ac-commodation and tuition costs. To address these difficulties, most students combine work and study. The most flexible occupations were found to be in the delivery and taxi sectors, allowing students to maintain high class attendance. Financial literacy and the ability to manage expenses are becoming key skills for the successful adaptation of students to new conditions.